Tonic Dopaminergic Stimulation Impairs Associative Learning in Healthy Subjects - Breitenstein, Caterina; Korsukewitz, Catharina; Flöel, Agnes; Kretzschmar, Timo; Diederich, Kai; Knecht, Stefan (Neuropsychopharmacology (New York, N.Y.), 2006)
Endogenous dopamine plays a central role in salience coding during associative learning. Administration of the dopamine precursor levodopa enhances learning in healthy subjects and stroke patients. Because levodopa increases both phasic and tonic dopaminergic neurotransmission, the critical mechanism mediating the enhancement of learning is unresolved. We here probed how selective tonic dopaminergic stimulation affects associative learning. Forty healthy subjects were trained in a novel vocabulary of 45 concrete nouns over the course of 5 consecutive training days in a prospective, randomized, double-blind, placebo-controlled design. Subjects received the tonically stimulating dopamine-receptor agonist pergolide (0.1 mg) vs placebo 120 min before training on each training day. The dopamine agonist significantly impaired novel word learning compared to placebo. This learning decrement persisted up to the last follow-up 4 weeks post-training. Subjects treated with pergolide also showed restricted emotional responses compared to the PLACEBO group. The extent of 'flattened' affect with pergolide was related to the degree of learning inhibition. These findings suggest that tonic occupation of dopamine receptors impairs learning by competition with phasic dopamine signals. Thus, phasic signaling seems to be the critical mechanism by which dopamine enhances associative learning in healthy subjects and stroke patients.